Academic choices and motivation: Diverse groups in Israel. Issue 5 (3rd September 2017) - Arar, Khalid; Abramovitz, Ruth; Bar-Yishay, Hanna; Notzer, Neta
Abstract: Israel is a multi-cultural society with a Jewish majority and a large Arab minority. This study aims to examine whether Israeli Arab and Jewish students have different motivations and consider different factors when choosing a college for postgraduate studies. A case study, during the academic year 2010–11 administered questionnaires to 290 Jewish and Arab postgraduate students in a private academic college in order to investigate students' motivations for postgraduate studies and choice of college. Findings indicated that the strongest motivation expressed by all the students is a desire for self-fulfilment. Motivation for social mobility and to help to empower their society is more important for Arab students. Convenience considerations (proximity to home, flexible entrance standards and employment prospects while studying) determined college choice for Jews and Arabs more than college reputation and teaching quality. Yet Arab students attach more importance than Jewish students to the college's quality. It is concluded that postgraduate programmes should be more sensitive to diverse students' needs.